Establishment of Femoral Bone Defect Model in Sprague-Dawley Rat for Engineered Scaffold Implantation: A Pilot Study - Amira Raudhah Abdullah; Intan Maslina Musa (Springer, 2024)
Indexed by WOS/ Scopus